Prematurity and Low Birth Weight and Their Impact on Childhood Growth Patterns and the Risk of Long-Term Cardiovascular Sequelae - Iwona Jańczewska; Jolanta Wierzba; Alicja Jańczewska; Małgorzata Szczurek-Gierczak; Iwona Domżalska-Popadiuk (MDPI AG, 2023)
Preterm birth (before 37 completed weeks of gestation) is a global health problem, remaining the main reason for neonatal mortality and morbidity. Improvements in perinatal and neonatal care in recent decades have been associated with a higher survival rate of extremely preterm infants, leading to a higher risk of long-term sequelae in this population throughout life. Numerous surveillance programs for formerly premature infants continue to focus on neurodevelopmental disorders, while long-term assessment of the impact of preterm birth and low birth weight on child growth and the associated risk of cardiovascular disease in young adults is equally necessary. This review will discuss the influence of prematurity and low birth weight on childhood growth and cardiovascular risk in children, adolescents and young adults. The risk of cardiovascular and metabolic disorders is increased in adult preterm survivors. In early childhood, preterm infants may show elevated blood pressure, weakened vascular growth, augmented peripheral vascular resistance and cardiomyocyte remodeling. Increased weight gain during the early postnatal period may influence later body composition, promote obesity and impair cardiovascular results. These adverse metabolic alterations contribute to an increased risk of cardiovascular incidents, adult hypertension and diabetes. Preterm-born children and those with fetal growth restriction (FGR) who demonstrate rapid changes in their weight percentile should remain under surveillance with blood pressure monitoring. A better understanding of lifelong health outcomes of preterm-born individuals is crucial for developing strategies to prevent cardiovascular sequelae and may be the basis for future research to provide effective interventions.